Santālī de ujāṛe dī dāsatāna: sharanārthīāṃ dīāṃ waṇḍa sambandhī yād - Talbot, Ian.; Tatla, Darshan Singh. (Title on t.p. verso:Santali de ujarhe di dastan, 2007)
Partition of Punjab, 1947; transcript of interviews with some of the survivors.
Includes bibliographical references (p. 249-269).
Partition of Punjab, 1947; transcript of interviews with some of the survivors.
In Panjabi.
Keywords: Punjab (India) / History / Partition, 1947 / Personal narratives.; Punjab (India) / History / Partition, 1947 / http://id.loc.gov/authorities/subjects/sh85109125